Peran ESG dan Tata Kelola Perusahaan dalam Mengendalikan Manajemen Laba: Bukti Empiris dari Perusahaan Manufaktur Indonesia - Seti Seti; Rahma Yuliani; Monica Rahardian Ary Helmina (Journal of Economics and Management Scienties, 2026)
Earnings management remains a major concern as it reduces the quality of financial reporting and undermines stakeholders’ trust. Although Environmental, Social, and Governance (ESG) and corporate governance mechanisms are expected to restrain opportunistic managerial behavior, previous studies have reported inconsistent findings. This study examines the effects of ESG, managerial ownership, and independent commissioners on earnings management, with financial distress as a moderating variable. The study employed a quantitative approach using data from manufacturing companies listed on the Indonesia Stock Exchange in 2024. A total of 167 companies were selected through purposive sampling after outlier treatment. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with IBM SPSS Statistics 29. The results show that ESG, managerial ownership, and independent commissioners have a negative and significant effect on earnings management. Financial distress does not moderate the relationships between ESG and earnings management or between managerial ownership and earnings management. However, financial distress significantly moderates the relationship between independent commissioners and earnings management. These findings highlight the importance of ESG implementation and corporate governance in improving financial reporting quality, while emphasizing the strengthened monitoring role of independent commissioners under financial distress.